A systemic proposal for the evaluation of the education inspectorate of the Community of Madrid - Morales Gómez, Adoración (Avances en Supervisión Educativa, 2024)
The evaluation of public institutions has always been a delicate aspect that is difficult to address, however, it is still necessary in a context where the principles of transparency, improvement of public services and citizen service are an essential component in current public administration. This article presents the evaluation proposal for the educational inspection of the Community of Madrid designed ad hoc by a team of inspectors who were entrusted with the preparation of the internal and external evaluation of this public service. To this end, the different procedures developed and their main characteristics are explained, based on a model that tries to homogenize a rigorous, useful, pragmatic and realistic system.